(untitled) (Foro: Revista de Derecho, 2017)
El reconocimiento de la jurisprudencia como fuente jurídica principal concede a todo fallo efectos vinculantes de alcance general y abstracto. Este cambio de esquema ha trastocado los cánones de tradición romano-germánica. La ubicación de la jurisprudencia dentro del sistema de fuentes dependerá, por la forma, de la jerarquía orgánica del juez o tribunal del que emanare. En cuanto al fondo, existen dos aristas. La primera, en cuanto a la materia, en aplicación del principio del paralelismo de las formas jurídicas: si existiese reserva constitucional o legal sobre una materia determinada, la jurisprudencia estará creando subreglas de idéntica naturaleza y jerarquía. Finalmente, desde la perspectiva axiológica, en atención al principio de interpretación pro homine y de progresividad de los derechos fundamentales, la jurisprudencia que prevalecería es aquella que presente un estándar mayormente garantista, sin importar la jerarquía orgánica del juez o tribunal emisor. The acknowledgement of jurisprudence as a main source of law, confers every ruling mandatory effects with a general and abstract scope. The alteration in the traditional scheme of sources of law has changed around the customary canons of the Roman-Germanic tradition. The location of jurisprudence within the system of sources of law will depend, in regard to the form, on the organic hierarchy of the judge or tribunal. In regard to the substance, we must take into account two different scenarios. The first, referred to the subject, in which in light of the principle of parallelism among juridical forms: if there is constitutional or legal reserve over a determined matter, jurisprudence will create sub-rules of identical nature and hierarchy. In the second scenario, from an axiological perspective, in light of the pro homine interpretation principle and of the progressive interpretation of human rights, only that jurisprudence which establishes a higher guarantor standard will prevail, regardless of the organic hierarchy of the ruling judge or tribunal.